Letter from the Editor - Edmundo Mora (Asociación Colombiana de Profesores de Ingles, 2016)
Once again it is a real pleasure for the Editorial Committee of HOW to reach teachers of English in Colombia and some other parts of the world through this publication. Needless to say, HOW is the bond of ASOCOPI that keeps teachers of our country united concerning the goal of improving the standard of the teaching of English in Colombia.